Preference Evaluation System for Construction Products Using QFD-TOPSIS Logic by Considering Trade-Off Technical Characteristics. (26th January 2017) - Cho, Jaeho; Chun, Jaeyoul; Kim, Inhan; Choi, Jungsik
Abstract : This paper investigates the feasibility of quality function deployment, technique for the order of preference by similarity to ideal solution (QFD-TOPSIS) in presenting user preferences for multiple alternatives, such as construction technologies, products, systems, and design solutions, with trade-off technical characteristics (TC). The original QFD as house of quality (HOQ) defines the requirements and features as subjective matrix relations, which cause interpretations to vary across users and limit its industrial applications. QFD-TOPSIS is a new model that combines the benefits of QFD with those of TOPSIS, maintains the subjectivity and objectivity evaluation of the technical characteristics (TC), and rates the preferences by considering users' individual propensity for requirements. In addition, QFD-TOPSIS rates the preferences through the reciprocal compensation effects of trade-off TC and filters unsuitable alternatives with predefined restrictive conditions. Trade-off refers to conflicts and/or contradictions between attributes, often arising in multicriteria decision-making. Users or project stakeholder groups define the priorities of trade-off TC that directly influence product preferences and decision-making. In the present study, we have developed a Web system based on the QFD-TOPSIS logic and tested its operation to verify its industrial applicability and viability for automatic quality evaluation.